2021
DOI: 10.1186/s43094-020-00168-1
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, phytochemistry, and pharmacological activities of Cochlospermum tinctorium A. Rich (Cochlospermaceae): a review

Abstract: Background The plant Cochlospermum tinctorium A. Rich is a sub-shrub that belongs to the family Cochlospermaceae. The plant has been used in traditional medicine for the treatment of malaria, rickets, stomachache, diarrhea, gastric ulcer, parasitic infestations, liver diseases, fever, pain, inflammation, infectious diseases, epilepsy, snake bite, burns, orchitis, labour, menstrual problems, and many other diseases. This review summarizes the traditional uses, phytochemistry, and pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Used to treat liver disease, syphilis, measles, yellow fever, boils, fever and abdominal pain [137] . Decoction and powder of root are used to treat hepatitis in Burkina Faso [15] Acute oral administration of root extract at 500 mg/kg did not induce toxic effect [137] Yellow fever Hepatitis Combretum glutinosum Perr. Used to treat hepatic disease in Africa [24] and malaria in Senegal [138] .…”
Section: Discussionmentioning
confidence: 99%
“…Used to treat liver disease, syphilis, measles, yellow fever, boils, fever and abdominal pain [137] . Decoction and powder of root are used to treat hepatitis in Burkina Faso [15] Acute oral administration of root extract at 500 mg/kg did not induce toxic effect [137] Yellow fever Hepatitis Combretum glutinosum Perr. Used to treat hepatic disease in Africa [24] and malaria in Senegal [138] .…”
Section: Discussionmentioning
confidence: 99%
“…Even though there has been advancement in drug development procedures for use against ailments, still various diseases continue to affect the global population with significant death (Thomford et al, 2018). The herbal plants and their derivatives have been utilized in traditional practice by many people globally and serve as the main source of remedies against many diseases (Ahmad et al, 2021). It has been reported that about 80% of the global population utilizes herbal plants preparations as their significant cure to many pathological conditions (Kale et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there have been challenges to using herbal products such as defective standardization and dosage, insufficient identification and isolation, lack of clinical and toxicological profile of various medicinal plants (Okaiyeto & Oguntibeju, 2021; Thomford et al, 2018) such as Acacia sieberiana . As such, qualitative scientific evaluations on the harmful consequences of herbal plants and their derivatives used in traditional practice are required to develop new, effective and safe therapeutic agents (Ahmad et al, 2021; Ukwuani et al, 2012). Besides, the scientific information of herbal plants’ short and long term safety profiles is essential to document the safety concern of such plants for efficient therapeutic reasons (Reduan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have contributed to the general health and well-being of the populace for a long time [2]. About 75% of the people globally depend on traditional medicine for their basic health requirements [9]. Many therapeutic compounds employed in orthodox medicine originate from plants [10].…”
Section: Introductionmentioning
confidence: 99%